The Effect of Workload and Work Stress on Employee Performance at the Main Hall of the Pompengan River Area of Jeneberang Makassar - Sri Nurhidayat; Edi Jusriadi; Sahabuddin N (Pustaka Digital Indonesia, 2026)
This study aims to examine the effect of workload and work stress on employee performance at the Pompengan Jeneberang River Basin Center in Makassar. The research was motivated by increasing work demands and rising employee absenteeism, which served as organizational indicators requiring further investigation, although absenteeism was not directly assumed to represent a decline in performance. This study employed a quantitative approach involving 104 respondents from a population of 141 employees, with the sample size determined using the Slovin formula. Data were collected through questionnaires, observation, interviews, and documentation, and were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results show that workload has a positive and significant effect on employee performance, while work stress has a negative and significant effect. The coefficient of determination (R²) of 0.392 indicates that workload and work stress explain 39.2% of the variation in employee performance, while the remaining 60.8% is explained by other factors outside the model. This finding suggests that the model has moderate explanatory power and that employee performance is influenced not only by workload and stress but also by other organizational and individual factors. The findings indicate that a proportional and well-managed workload can support employee productivity, responsibility, and task completion. Conversely, excessive work stress may reduce concentration, work effectiveness, and overall performance. Therefore, public sector organizations need to implement fair workload allocation, clear task distribution, reasonable deadlines, and stress management strategies to maintain employee performance. In conclusion, workload and work stress are important factors associated with employee performance, and their proper management is essential for improving organizational effectiveness.